Description of Differences in Sexual Desire in Female Fujoshi Kpop Fans in Indonesia Based on Age - Safna Oktavieri; rahayu hardianti utami (In Trend : International Journal of Trends in Global Psychological Science and Education, 2024)
In recent years, people's interest in the Korean wave phenomenon has increased. This can be seen from the large number of people, especially young people, who are fans of this Kpop idol. The majority of Kpop fans are dominated by women. Most of these female Kpop fans are also fujohi. Fujoshi is a term for women who like relationships with men. From this phenomenon, fans claim that viewing fujoshi-related content can increase their sexual desire. Therefore, the aim of this research is to see a picture of the differences in Sexual Desire or sexual desire in female fujoshi kpop fans when viewed in terms of age, namely teenagers and adults. This research is quantitative research with a descriptive method carried out on 92 respondents. Data analysis in this study used the homogeneity test and the Mann Whitney U-test. The results obtained are that the significance value in the homogeneity test shows the number 0.078, which means the data in this study is homogeneous. In the Mann Whitney U-test, the significance value was 0.000 with a mean rank for adolescents of 28.02 and for adults of 64.98. This means that there are differences in the variables in the research data.